The ethical issues surrounding artificial intelligence - Alsahafi, Omar; Alfaleh, Abdulrahman; Altamimi, Mshary; Alghamdi, Ahmed; Alhafi, Abdullah; Altigani, Abdelrahman; Elsadig, Muawia A.; Sulieman, Sulieman Mohamed Ali; Mohamed, Yasir Abdelgadir (Edelweiss Applied Science and Technology, 2024)
Ethical issues center themselves around Artificial Intelligence (AI) and the various opportunities and threats that it offers. The purpose of this research paper is to explain the positive side of AI, as well as the problems that require addressing. The actual study starts with the aims and objectives of the research and briefly highlights the importance of the research topic, the operational definitions of the terms under study, and the conceptual framework. It covers the history of AI, development in technology, and consequences on society. The benefits and the disadvantages of AI are included in the evaluation of its impact on specific sectors. Social consequences are considered, with an emphasis on how the application of AI will influence social structures and groups. The legal issues are considered, turning to the existing legislation and the possible legal repercussions. Ethical issues are considered with a focus on the proper use of artificial intelligence systems. Finally, the general ideas developed in the research are briefly highlighted, the thesis is repeated, and attention is drawn to the fact that further investigation and prevention efforts are required to tackle AI’s ethical issues. The findings of the study are then followed by suggestions for future work in this area.